Laboratory Study of High-Resistance Laterite-Based Geopolymer Bricks - Mollaei, Somayeh; Marabi, Yaser; Fahmi, Ahmad; Babaeian , Ali Reza (International Journal of Integrated Engineering, 2022)
A high amount of energy is required to produce different types of clay and sand-lime bricks, and a huge amount of carbon dioxide is released into the atmosphere. Also, brick waste from the destruction of dilapidated buildings pollutes the environment. Application of pozzolanic sources containing aluminosilicate and alkaline activators can be beneficial in production of geopolymer bricks, which do not need to be baked in a furnace and can be recycled. A laterite-based geopolymer brick mix design was introduced in this study as an environmental-friendly material. This type of brick is produced using available and cheap raw materials without the need for high furnace heat. The raw materials included laterite soil as aluminosilicate, laterite aggregate filler passed through sieve No. 8 and an alkaline activating solution with different concentrations. The effect of sieve size for laterite soil screening on the compressive strength of these brick samples was investigated. The results showed that the compressive strength of the prepared bricks here was much higher than the recommended standards for construction bricks and was similar to those of high-resistance bricks. The size of laterite soil sieves had a significant effect on the compressive strength of geopolymer brick samples. The percentage of water absorption of the bricks with different concentrations of alkali activating solution was also within the recommended range for construction bricks.